The Guncle : a novel - Rowley, Steven, 1971- (New York : G. P. Putnam's Sons, 2021)
"From the bestselling author of Lily and the Octopus and The Editor comes a warm and deeply funny novel about a once-famous gay sitcom star whose unexpected family tragedy leaves him with his niece and nephew for the summer"--.